The Influence of Legal Education, Judicial Performance, Police Accountability, And Community Perceptions Of Crime Prevention In Indonesia - Heri Heriyanto (Westscience Press, 2023)
Crime prevention is a critical issue for governments around the world, and Indonesia is no exception. Legal education, judicial performance, police accountability, and community perceptions are all important factors in crime prevention in Indonesia. This study examines the relationship between these factors and their impact on crime prevention in Indonesia. The study uses a mixed-methods approach, including both quantitative and qualitative data, to analyze the relationship between legal education, judicial performance, police accountability, and community perceptions of crime prevention in Indonesia. The study found that legal education, judicial performance, police accountability, and community perceptions are all critical factors in crime prevention in Indonesia. The study highlights the need for more investment in legal education programs, for improved judicial performance, for greater police accountability, and for more community-based crime prevention programs.